Evaluating the effectiveness of dialectical behavior and motor perception training on the symptoms of attention deficit, cognitive avoidance and working memory of female students with attention deficit/hyperactivity disorder - Siraei, Fatemeh; Bigdeli, Hossein (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Attention Deficit/Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders that is observed in early childhood. The aim of this study was to investigate the effectiveness of dialectical behavior and cognitive motor training on attention deficit, cognitive avoidance and working memory in female students with attention deficit/hyperactivity disorder. Materials and Methods: The present study was quasi-experimental with pretest-posttest design. The statistical population consisted of 257 elementary school girls with attention deficit hyperactivity disorder and resident in district 2 of Tehran. Each meeting was given to participants. Data were collected using Cognitive Avoidance Questionnaire, Attention Deficit Disorder Scale and Wechsler Working Memory Test. Dialectical behavioral therapy sessions were held in 10 sessions and 12 sessions of cognitive and motor training were held in 12 one-hour sessions each week. For dialectical behavior therapy sessions, protocol therapy (Linehan, 1993) and McGinn Cognition and Motor Training (1970) were used. Data were analyzed using multivariate analysis of covariance and SPSS 27 software. Findings: The results showed that there was no significant difference between the experimental and control groups of cognitive avoidance, attention deficit and working memory including cognitive avoidance (P=0.672, F=0.40), attention deficit (F=0.04, P=0.442), working memory (P=0.477, F=0.75). Conclusion: It can be concluded that there is no significant difference between dialectical behavior therapy and cognitive and motor training on cognitive avoidance, attention deficit and working memory.